Implementasi Kebijakan Badan Usaha Milik Desa Pandan Ningan di Desa Pendingan Kabupaten Musi Rawas - Apsas Saputra; Budi Puspo Priyadi; Teuku Afrizal; Retno Sunu Astuti (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
Based on the Village Ministerial Regulation Number 4 of 2015 concerning the establishment and management of BUMDes, each village is required to have a business entity managed by the village government. This paper aims to determine the implementation of the Pandan Ningan Village Owned Enterprise policy in providing LPG gas in Pendingan Village, Musi Rawas Regency. The problem is focused on the people of Pendingan Village who do not have gas cylinders personally. This research uses implementation theory from George C Edward III. The research method used in this research is descriptive qualitative method. Sources of data obtained from primary data and secondary data, data collection techniques through observation, interviews, documentation. The results of this study indicate that the implementation of the policy of the Pandan Ningan Village-owned business entity in providing LPG gas in Pendingan Village, Musi Rawas Regency is said to be good, this is because the Pandan Ningan Village-Owned Enterprise can meet the needs of the community. In addition, indicators from Edward III's theory are very suitable to be used and implemented in research. Of the four indicators, there are two indicators that can be said to be optimal.